The Effect of Tax Planning to Minimize the Tax Burden: A Case Study on an Employee Koperasi at PT.KBX - Melfrida, Christina; Malau, Melinda; Sihombing, Salmon (Fundamental Management Journal, 2016)
This study aims to determine how the effect of tax planning undertaken by PT. KBX, and to know what the right method to minimize the tax burden. The data for this study were obtained from interviews with tax accounting section and General Human Resources of PT. KBX with observations regarding the implementation of tax planning. The research proves that PT. KBX has not executed tax planning appropriately. The company uses the method of calculation of income tax Article 21 is borne by the employer (net method), so that the expense incurred income tax Article 21 shall be paid in the calculation of taxable income for corporate income tax. As a result the corporate income tax paid is greater.Keywords : Taxes, PT. KBX, Peghasilan Tax (VAT).